2021
DOI: 10.1093/schbul/sbaa156
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Glutamate on Switching to Clozapine in Treatment-Resistant Schizophrenia

Abstract: It has been suggested that the antipsychotic clozapine may modulate brain glutamate, and that this effect could contribute to its efficacy in treatment-resistant schizophrenia (TRS). The aim of this study was to examine the effects of clozapine on brain glutamate in TRS longitudinally. This study examined individuals with TRS before and 12 weeks after switching from a non-clozapine antipsychotic to treatment with clozapine as part of their normal clinical care. Proton magnetic resonance spectroscopy (1H-MRS) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 56 publications
3
40
2
Order By: Relevance
“…In line with our previous report in the same cohort 69 , SPC of caudate Glu corr and NAA corr significantly differed from zero, with lower levels after 12 weeks of clozapine treatment (Glu corr : T 20 = 3.04; P = 0.006; NAA corr : T 20 = 2.43; P = 0.03; Table 1 ). There was no significant change in ACC SPC in Glu corr and NAA corr ( P > 0.05, Table 1 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In line with our previous report in the same cohort 69 , SPC of caudate Glu corr and NAA corr significantly differed from zero, with lower levels after 12 weeks of clozapine treatment (Glu corr : T 20 = 3.04; P = 0.006; NAA corr : T 20 = 2.43; P = 0.03; Table 1 ). There was no significant change in ACC SPC in Glu corr and NAA corr ( P > 0.05, Table 1 ).…”
Section: Resultssupporting
confidence: 92%
“…While we detected reductions in caudate, but not ACC, glutamate during clozapine treatment in the same patient cohort 69 , in the current study we found no evidence to implicate changes in glutamate levels with cortical thinning or caudate volume reduction. Instead, reductions in caudate volume during clozapine treatment were associated with local reductions in NAA, which may indicate decreases in the integrity of neurons or oxidative metabolism in mitochondria 76 79 .…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Increased synaptic glutamate levels due to decreased GLAST membrane expression in NHE9 mutations is consistent with increased synaptic glutamate levels [73][74][75][76][77][78][79][80]. Antipsychotic drugs reduce the increased synaptic levels of glutamate [74,146].…”
Section: Nhe6 and Nhe9mentioning
confidence: 73%
“…121 Further, olanzapine, risperidone and other antipsychotics appear to have different effects on biobehavioural changes induced by phencyclidine, suggesting that these medications may exert a different action on NMDA receptors. 122,123 Finally, clozapine, which has been shown to be the only effective antipsychotic for treatment-resistant patients, modu lates glutamatergic activity that has been correlated with the degree of symptomatic change, 124 further supporting the idea of other mechanisms underlying its therapeutic effects. 119,[125][126][127] It is possible that a more general systems-level explanation may lie in the possibility that antipsychotic medication exerts its effect by altering the cortical E/I balance in patients with schizophrenia.…”
Section: Effects Of Medicationmentioning
confidence: 94%